(untitled) (Cadernos de Sociomuseologia, 2022)
The article presents the MAR - Agricultural Museum of Riachos (1989) based in a former Olive Factory and Agricultural House, owned by the Lawyer and Farmer, José Marques, one of its founders. Nowadays, the building belongs to Torres Novas’ Municipality. This space of memory and real experiences reaches the community, local and globally, defining itself as a real Community Museum. Founded under the ideals of Sociedade dos Cingeleiros’ mutualist legacy, its roots are established under in the sacred and profane expression of Festa da Bênção do Gado, which aroused the birth of MAR. The museum is managed under an inclusive vision and a cultural commitment that merges Tradition and Contemporaneity. Harmonizing Cultural Animation with Applied Scientific Research is the main challenge for the institution. Key words: Community Museum; Rurality; Festivities; Sociomuseology; Contemporaneity